2013
DOI: 10.1111/apa.12266
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition of growth abnormalities permitting early intervention

Abstract: Normal growth is a sign of good health. Monitoring for growth disturbances is fundamental to children's health care. Early detection and diagnosis of the causes of short stature allows management of underlying medical conditions, optimizing attainment of good health and normal adult height.ConclusionThis review summarizes currently available information on monitoring for short stature in children and conditions usually associated with short stature and summarizes the authors’ conclusions on the early recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 48 publications
3
68
0
3
Order By: Relevance
“…Growth failure and short stature in childhood are often early symptoms of an underlying disorder requiring appropriate diagnosis and management to achieve individual growth potential [1, 2]. Human recombinant growth hormone (GH) therapy is an approved treatment for a number of growth-related conditions, most commonly GH deficiency (GHD).…”
Section: Introductionmentioning
confidence: 99%
“…Growth failure and short stature in childhood are often early symptoms of an underlying disorder requiring appropriate diagnosis and management to achieve individual growth potential [1, 2]. Human recombinant growth hormone (GH) therapy is an approved treatment for a number of growth-related conditions, most commonly GH deficiency (GHD).…”
Section: Introductionmentioning
confidence: 99%
“…4 Further evaluation of pathological short stature is done as per various etiologies. 5,6 Familial short stature and Constitutional Growth delay are considered as normal variants. 7 While the pathological short stature includes a wide variety of underlying disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO has also developed growth monitoring charts; and a training course is available to help in assessing child growth [39]. Haymond et al suggested that, for a good differential diagnosis, it is essential to get medical history, family history, physical examination, analysis of the growth curve, and weight-for-height measurements [40]. A review by Nwosu and Lee on evaluation of short and tall stature in children suggested that firstly a thorough history and physical examination should be conducted and the laboratory investigations should then be based on the finding of these examinations [1].…”
Section: Resultsmentioning
confidence: 99%